PERENCANAAN DIKLAT BAGI PTK-PNF - Samto Samto (JIV-Jurnal Ilmiah Visi, 2007)
The improvement of the quality of nonformal educators and educational personnel of nonformal educators can be conducted in several ways. One of them is through training programs. Trainings are effective, though they need a lot of financial support. In order to be effective, budget regarding the training programs should be carefully planned. The diversity of educators and educational personnel affect the structure of training curricula. In order to solve problems in practice, the design of the curricula should be needs-oriented. This would result a competency-based, goalbased curricula, and problem-based curricula.